Commercial systems of Znata tribe in the Middle Maghreb during the middle Ages - Boumankar, Mouad; Abed, Youcef (Journal of Human Sciences, 2021)
The Znata tribe is one of the largest Berber tribes in the Middle Maghreb. It is characterized by its wide geographical location, and the multiplicity of its ascendants, which affected its economic and notably commercial life during the middle ages, as Znata’s commerce during that time wasthe most important economic activityin the Middle Maghreb, whose impact and influence was apparent on other domains.Through the research of Znata’s commercial systems,we can draw a picture of the commercial movements during that period, by standing on the most important ways and trade routes of Znata.Whether the internal paths, that link Zenata to the metropolitan areas of the Maghreb, or trade routes that link the tribe to the Near and Far Maghreb, or to Europe and Western Sudan.Moreover, we seek to know the types of Znata markets and the standards by which these markets have been divided, as well as addressing Znata currency that has been used, and expose the phenomena of lower and higher prices, and the diversity of Znata’s weights and measures, without dismissing the treasurers and their role in the market.